2002
DOI: 10.1159/000064787
|View full text |Cite
|
Sign up to set email alerts
|

Ranging Behavior, Group Size and Behavioral Flexibility in Ethiopian Hamadryas Baboons (Papio hamadryas hamadryas)

Abstract: This study reports group size, home range size, daily path lengths, seasonal effects on ranging behavior and qualitative information on diet for a population of hamadryas baboons inhabiting the lowlands of the northern Rift Valley in central Ethiopia. The minimum home range size and daily path length for this population are similar to those reported for other populations of hamadryas baboons in Ethiopia and Saudi Arabia. Group sizes, however, are much larger than those in most other hamadryas populations for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 17 publications
1
74
1
2
Order By: Relevance
“…On the other hand, social relationships between females within the same harem do not appear to be as dependent on kinship as in gelada baboons. These comparisons are only tentative because Guinea baboons have so far been mostly studied in captivity and because recent studies of new wild populations of gelada and hamadryas baboons have suggested that the social organization of these species is more variable than previously thought [Mori et al, 1999;Swedell, 2002aSwedell, , 2002b. More field studies of these 3 spe-cies are needed to fully understand the similarities and differences in their mating system and social organization and explain them on the basis of their phylogenetic history and ecological adaptations.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, social relationships between females within the same harem do not appear to be as dependent on kinship as in gelada baboons. These comparisons are only tentative because Guinea baboons have so far been mostly studied in captivity and because recent studies of new wild populations of gelada and hamadryas baboons have suggested that the social organization of these species is more variable than previously thought [Mori et al, 1999;Swedell, 2002aSwedell, , 2002b. More field studies of these 3 spe-cies are needed to fully understand the similarities and differences in their mating system and social organization and explain them on the basis of their phylogenetic history and ecological adaptations.…”
Section: Discussionmentioning
confidence: 98%
“…Its unusual multilevel social system and male-dominated social organization are commonly thought to be evolutionary adaptations to the semi-desert environment in which it likely evolved, either in the Horn of Africa eral habitat types but is predominantly a semi-desert scrubland dominated by shrubby Acacia and Grewia [Swedell, 2002b;Abule et al, 2007] broadly similar to the habitat of hamadryas baboons in other parts of their geographic range [Sigg and Stolba, 1981;Biquand et al, 1992]. Other habitat types within the range of the Filoha population include grasslands and swamps dominated by Sporobolus and Cyperus grasses and small forests of doum palm trees (H. thebaica) .…”
Section: Introductionmentioning
confidence: 99%
“…The two wettest months of the year are usually July and August, and the driest and hottest months of the year are usually May and June, just prior to the onset of the long rains [Swedell, 2002b[Swedell, , 2006. The annual rainfall is 500-600 mm, with the vast majority of this falling during July and August ( table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…These ranging and social patterns have often been attributed to the scarce and widely dispersed distribution of food resources in their semi-desert habitats (Kummer 1968;Sigg & Stolba 1981;Swedell 2002Swedell , 2006Schreier 2010;Schreier & Swedell 2012a). Hamadryas Baboons rely on Acacia species for subsistence throughout their range (Kummer 1968;Nagel 1973;Kummer et al 1981;Al-Safadi 1994;Schreier 2010).…”
Section: Introductionmentioning
confidence: 99%